2014
DOI: 10.5455/ijmsph.2014.150820142
|View full text |Cite
|
Sign up to set email alerts
|

Polymerase Chain Reaction using the MPB64 fragment for detection of mycobacterium tuberculosis complex DNA in suspected TB cases

Abstract: Background: Various primers have been used for detection of Mycobacterium tuberculosis complex (MTBC) DNA using Polymerase chain reaction (PCR). The MPB64 gene has been demonstrated to be a highly specific target for MTBC detection. Aims & Objectives: To detect MTBC DNA using MPB64 primers in clinical specimens of Nepalese patients suspected to have tuberculosis (TB). Materials and Methods: DNA was extracted from 44 clinical specimens of patients suspected of having TB and MPB64 targeted PCR was performed. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
(15 reference statements)
0
3
0
Order By: Relevance
“…Another diagnostic target sequence which many studies are based on, is mpb64 [ 28 , 37 , 38 ]. This sequence has 687 bp length [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another diagnostic target sequence which many studies are based on, is mpb64 [ 28 , 37 , 38 ]. This sequence has 687 bp length [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, MPB64 has been demonstrated to be highly specific for Mycobacterium tuberculosis complex [23] and other studies have reported sensitivity and specificity of 75e90% and 100% respectively [9,10,19,23]. The literature regarding the evaluation of MPB64 in patients of TBM in our region is scanty [9,24].…”
Section: Introductionmentioning
confidence: 88%
“…MPB64 primer targets and amplifies the gene MPB64, producing 240 bp product and IS6110 primer amplifies insertion sequence IS6110 of M. tuberculosis complex, which produces 123 bp product. Primers for both sequences were opted from previous studies [6,9,15] and the PCR conditions were optimized for multiplex PCR. The primers were analyzed using NCBI BLAST with insertion sequence IS6110 (Gene bank ID KP844721.1) and MPB64 gene (Gene bank ID 885925) before using them.…”
Section: Amplification Of Dnamentioning
confidence: 99%